Quantitative Optical Coherence Tomography Angiography Detects Retinal Perfusion Changes in Carotid Artery Stenosis - Pierro, Luisa; Arrigo, Alessandro; De Crescenzo, Michele; Aragona, Emanuela; Chiesa, Roberto; Castellano, Renata; Catenaccio, Barbara; Bandello, Francesco (Frontiers in Neuroscience, 2021)
Background: Carotid artery stenosis (CAS) is a multifaceted disease characterized by possible ocular involvement. Treatment with carotid endarterectomy helps to restore cerebral perfusion which may prevent ocular and cerebral complications. The main aim was to assess retinal and choroidal vascular perfusion changes before and after endarterectomy in patients affected by CAS. Methods: The design of the study was prospective, observational, including patients affected by CAS and healthy controls. The follow-up was 3-months. We performed quantitative optical coherence tomography (OCT) angiography (OCTA) analyses of retinal perfusion changes, before and after endarterectomy. The main outcome measures were the quantitative changes of choroidal thickness (CT), retinal nerve fiber layer (RNFL) and ganglion cell layer (GCL); vessel density (VD) and vessel tortuosity (VT) OCTA metrics were also measured. Results: Sixty eyes of 30 patients affected by CAS and 30 eyes of 30 controls were included. We separately considered the ipsilateral eyes to CAS, the contralateral eyes to CAS and the healthy eyes. Visual symptoms were absent in all the patients. RNFL and GCL resulted similar between patients and controls (p>0.05). CT was significantly thinner in ipsilateral eyes than controls (p<0.01) and it resulted unchanged after surgery (p>0.05). VD resulted significantly altered only in some plexa of the ipsilateral eyes (p<0.01), whereas VT disclosed decreased values of the entire retinal vascular network, both in ipsilateral and contralateral eyes (p<0.05). Endarterectomy was followed by statistically significant improvement of retinal perfusion (p<0.05). Conclusions: OCTA can non-invasively detect post-endarterectomy retinal perfusion improvements in CAS patients with baseline diabetes and hypertension as a systemic risk factor.